Dentist's Role and Responsible in Identification and Investigation - Kurniawan, Arofi; Chusida, An'nisaa; Satigi, Lyvia Vanessa; Romadhoni, Ajeng Dyah; Liandro, Muhammad Raihan; Margaretha, Mieke Sylvia; Utomo, Haryono; Marini, Maria Istiqomah; Rizky, Beta Novia; Roosyanto Prakoeswa, Beshlina Fitri Widayanti (Indonesian Journal of Dental Medicine, 2021)
Background: A dentist is responsible for promoting oral health and disease prevention to make the world a better place in terms of oral health. Besides, the dentist also plays an important role in the forensic field and law enforcement. Forensic odontology is an area of dentistry that deals with the proper management and investigation of dental evidence, which aids in identifying people and the presentation of dental evidence in the interest of justice. Purpose: This article discussed the role and responsibilities of dentists in human identification. Review: The world continues to deteriorate as time passes with much criminality and disasters that cannot be prevented. In many cases, the identification process can be done through the unique characteristics of dentition. Various information such as age, sex, and ethnicity are recorded in the tooth. Forensic dentists are responsible to manage and evaluate tooth evidence. Conclusion: Forensic odontology plays an essential role in determining individual identity. The unique features of dentition provide accurate results in identification if all procedures are correctly employed. With the advancement of science and technology, dentistry may now assist in the identification and investigation of forensic cases.